Retraction: Efforts to Overcome Cyber Crime Actions in Indonesia (J. Phys.: Conf. Ser.1114 012081). (7th February 2019) - Hatta, Muhammad; Rajamanickam, Ramalinggam; Abdullah, Dahlan; Hartono, H; Bunga, Marten; Adji, Hari Sapto; Amiruddin,; Djanggih, Hardianto; Hipan, Nasrun; Salle, S; Salmawati, S; Azis, Abdul; et al.
Abstract: This paper was retracted by IOP Publishing on 12 December 2018. This paper was published due to a technical error and was not intended to be included in this journal. Retraction published: 8 February 2019